Undoing gender - Butler, Judith, 1956- (Routledge, 2004)
Butler addresses the regulation of sexuality and gender that takes place in psychology, aesthetics, and social policy. These essays deepen her treatment of issues introduced by earlier work on the relationship between power and the body, the meaning & purpose of the incest taboo, and the problems of kinship.